2022
DOI: 10.1038/s41420-022-01098-y
|View full text |Cite
|
Sign up to set email alerts
|

Targeting mitochondrial one-carbon enzyme MTHFD2 together with pemetrexed confers therapeutic advantages in lung adenocarcinoma

Abstract: Metabolic remodeling is the fundamental molecular feature of malignant tumors. Cancer cells require sufficient energy supplies supporting their high proliferative rate. MTHFD2, a mitochondrial one-carbon metabolic enzyme, is dysregulated in several malignancies and may serve as a promising therapeutic candidate in cancer treatment. Here, our data confirmed that MTHFD2 gene and protein was upregulated in the cancerous tissues of LUAD patients and was correlated with a poor survival in LUAD. MTHFD2 was involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Especially enzymes of the mitochondrial one-carbon metabolism, SHMT2 and MTHFD2 are frequently increased in cancers, however, cancer cells can partly switch to the cytoplasmic isoforms for the generation of methylene-THF and thus the generation of one-carbon units [ 64 ]. In our study we found a robust enhancement of one-carbon metabolism enzymes but also the up-stream SSP enzymes in the two main subtypes of lung cancer on the mRNA level and an association of MTHFD1 and MTHFD2 gene expression with poor survival in lung adenocarcinoma, in line with previously published reports [ 22 25 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Especially enzymes of the mitochondrial one-carbon metabolism, SHMT2 and MTHFD2 are frequently increased in cancers, however, cancer cells can partly switch to the cytoplasmic isoforms for the generation of methylene-THF and thus the generation of one-carbon units [ 64 ]. In our study we found a robust enhancement of one-carbon metabolism enzymes but also the up-stream SSP enzymes in the two main subtypes of lung cancer on the mRNA level and an association of MTHFD1 and MTHFD2 gene expression with poor survival in lung adenocarcinoma, in line with previously published reports [ 22 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…In lung adenocarcinoma, the most frequent subtype of NSCLC, high PHGDH protein [ 24 ] and a high SSP enzyme mRNA expression [ 22 , 23 ] predicted poor overall survival. SHMT2 and methylenetetrahydrofolate dehydrogenase, MTHFD2, key enzymes of the mitochondrial folate cycle, were likewise found to be overexpressed in lung adenocarcinoma and/or associated with poor prognosis [ 23 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Actually, in the scenario of acute myeloid leukemia, specific MTHFD2 inhibitors potently and selectively repress cancer cell replication while protecting non-neoplastic lymphocytes [82]. To date, specific MTHFD2 inhibitors have shown impressive therapeutic efficacy in preclinical models of diverse cancer types, particularly exhibiting promising antitumor activities in lung adenocarcinoma cell lines, either as a single agent or in synergy with pemetrexed [44,[82][83][84].Considering the disparities in tumor metabolism and the immune microenvironment in distinct histologic subtypes of LUADs, metabolic targets represented by MTHFD2 hold promise for developing their application in histologic subtype-directed combinatorial immunotherapy. Notwithstanding, more efforts on exploring and validating the efficacy and clinical application protocols of MTHFD2 inhibitors in lung cancer are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs also regulate MTHFD2 expression. miRNA-99a-3p has been found to be an upstream regulator directly inhibiting MTHFD2 expression in lung adenocarcinoma ( Mo et al, 2022 ). In acute myeloid leukemia (AML), miR-92a could suppress cell proliferation by directly inhibiting MTHFD2 expression ( Gu et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%